2022
DOI: 10.21037/atm-22-4304
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic characteristics of Mycoplasma pneumoniae infection: a retrospective analysis of a single center in Suzhou from 2014 to 2020

Abstract: Background: Mycoplasma pneumoniae (M. Pneumoniae) is a common pathogen of respiratory tract infections, but there is still a lack of detailed investigation on the large sample of M. Pneumoniae infection in the all age population. And patients with severe M. Pneumoniae pneumonia (SMPP) still have a certain risk of death. How to identify the clinical characteristics and population of patients with SMPP as soon as possible is still an urgent problem in clinical practice. Methods: Demographic characteristics, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In recent years, prevalence of MPP has been on the rise, with annual increase of the severity rate, reaching as high as 42.6% in 2016 in Suzhou, China. 7 In the current study, we identified several characteristic clinical factors that might be associated with the development of severe MPP in children. These factors include age, decreased sounds of breathing, respiratory rate, fever duration, length of hospital-stay, co-infection with other pathogen(s), ferritin level, and LDH level.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, prevalence of MPP has been on the rise, with annual increase of the severity rate, reaching as high as 42.6% in 2016 in Suzhou, China. 7 In the current study, we identified several characteristic clinical factors that might be associated with the development of severe MPP in children. These factors include age, decreased sounds of breathing, respiratory rate, fever duration, length of hospital-stay, co-infection with other pathogen(s), ferritin level, and LDH level.…”
Section: Discussionmentioning
confidence: 99%
“…The caregivers had an average age of 35.1 ± 4.6 years, and most of them were female. A plausible explanation is the differences in immunity and social activities between men and women, and the fact that mother in Chinese families tend to care for children more and have closer contact with them [ 6 , 12 ]. Both groups had similar clinical symptoms, with fever and cough being the most frequent on admission.…”
Section: Discussionmentioning
confidence: 99%
“…Although older children and adolescents are mainly affected, infections and diseases caused by MP occur in all age groups [ 4 ]. Previous studies have reported that children and adults may have different manifestations of MPP, especially in terms of chest radiography findings [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2,8,[16][17][18] For the child population, most studies have reported a higher positive rate for children aged > 5 years than for those < 5 years old [1,2,[18][19][20] ; the same result was observed in our study, which showed that children under the age of 6 years had the highest infection rate, which is thought to be related to incomplete immune mechanisms in this group and was easily infected by M pneumoniae. [5,21] Some studies have shown sex differences in M pneumoniae infections, [1,5,22,23] with some showing no differences. [16,18] In this study, no difference was observed; although the positive rates of females were higher than those of males in all 3 methods, the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%